Deepening the understanding of wreck ecology: a comparative study of marine sediment microbiomes across 10 Maltese wreck sites - Bolton, Emma; Greenhalgh, Nadine; Kunselman, Emily; Mifsud, Jasmine; Patel, Neem; Sausmekat, Maja Pace; Oldach, Phoebe; Gambin, Timmy (Frontiers in Marine Science, 2024)
The anthropogenic influences of historical shipwrecks in the marine environment remain largely uncharacterized, particularly when looking at wrecks 50 metres deep that were lost over 80 years ago. Below 50 metres, light is reduced and the marine environment transitions from a euphotic to a mesophotic zone. At these depths, there are also significant changes in oxygen levels and pressure; these factors can contribute to a shift in microbial communities and metabolic pathways, providing insights into the adaptation and evolution of microorganisms. In this study, sediment samples were collected by a team of divers from across nine wreck sites varying in depth from 5 to 100 metres off the coast of Malta. All samples were collected with the consent and authorisation from the Government of Malta for the collection of marine genetic resources. The study used chemical analysis and metabarcoding to address how wrecks and associated influences shape microbial diversity and community composition in the surrounding environment. The alpha (ɑ) diversity of microbes was higher in the sediment next to the shipwrecks compared to the samples taken over 100m away from any wreck sites. Across all 9 of the wreck sites studied, sediment size proved to be the biggest driver of diversity, followed by frame type and oil leaks. This study shows wrecks that range in depth, frame type and country of origin can significantly influence the surrounding microbial ecosystem and sediment chemistry across different sediment types.